2017
DOI: 10.1038/s41537-017-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Progress in genome-wide association studies of schizophrenia in Han Chinese populations

Abstract: Since 2006, genome-wide association studies of schizophrenia have led to the identification of numerous novel risk loci for this disease. However, there remains a geographical imbalance in genome-wide association studies, which to date have primarily focused on Western populations. During the last 6 years, genome-wide association studies in Han Chinese populations have identified both the sharing of susceptible loci across ethnicities and genes unique to Han Chinese populations. Here, we review recent progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Schizophrenic patients have a reduced quality of life, significant functional impairment and suicide rates among schizophrenic patients remain alarmingly high ( Pompili et al, 2007 ). High heritability of schizophrenia has been consistently demonstrated by family studies ( Mäki et al, 2005 ) and genome-wide association studies have identified numerous risk chromosome loci candidates for schizophrenia ( O’Donovan et al, 2008 ; Purcell et al, 2009 ; Stefansson et al, 2009 ; Ripke et al, 2013 , 2014 ; Yue et al, 2017 ) indicating many common gene variants providing subtle effects ( Giusti-Rodríguez and Sullivan, 2013 ). Evidence from GWAS and studies revealing differentially expressed proteins in schizophrenia suggests that the majority of the pathophysiological processes underlying schizophrenia are involved in neuronal transmission, synaptic maturation and plasticity, neurite outgrowth and neurogenesis ( Hosak et al, 2012 ; Nascimento and Martins-de-Souza, 2015 ; Singh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenic patients have a reduced quality of life, significant functional impairment and suicide rates among schizophrenic patients remain alarmingly high ( Pompili et al, 2007 ). High heritability of schizophrenia has been consistently demonstrated by family studies ( Mäki et al, 2005 ) and genome-wide association studies have identified numerous risk chromosome loci candidates for schizophrenia ( O’Donovan et al, 2008 ; Purcell et al, 2009 ; Stefansson et al, 2009 ; Ripke et al, 2013 , 2014 ; Yue et al, 2017 ) indicating many common gene variants providing subtle effects ( Giusti-Rodríguez and Sullivan, 2013 ). Evidence from GWAS and studies revealing differentially expressed proteins in schizophrenia suggests that the majority of the pathophysiological processes underlying schizophrenia are involved in neuronal transmission, synaptic maturation and plasticity, neurite outgrowth and neurogenesis ( Hosak et al, 2012 ; Nascimento and Martins-de-Souza, 2015 ; Singh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…More substantial GWAS in Asian populations have gradually emerged over the past decade, with discovery sample sizes progressing from less than a thousand cases in some of the earliest studies (Ikeda et al, 2011;Yue et al, 2011) to over 13,000 in the most recent PGC analysis (Lam et al, 2018). The findings from schizophrenia GWAS in Asian populations have been broadly consistent with those of European populations (Yue et al, 2017). A recent study meta-analysed results from 8723 cases of Han Chinese ancestry and found associations at three loci, all of which had previously been found in European samples .…”
Section: Current Status Of Gwas In Schizophreniamentioning
confidence: 82%
“…Alkelai et al found that eight SNPs located in six genes ( LRRFIP1 , ACSL3 , LOC645434/NMBR , EFHD1 , UGT1A1 , and TWIST2 ) were associated with SZ in the Arab population of Israel 5 . Subsequent epidemiological studies reported that the heritability of SZ in Chinese population was approximately 63–78% 6 . Yue et al found two SNPs, viz.…”
Section: Introductionmentioning
confidence: 99%
“…5 Subsequent epidemiological studies reported that the heritability of SZ in Chinese population was approximately 63-78%. 6 Yue et al found two SNPs, viz. loc392301 and loc729457, in the Chinese Han population and replicated six SNP associations, including the apoptosis regulator, epigenetic PGBD1 and TSPAN18 genes, as well as neurodevelopmental ZKSCAN4 and NKAPL genes.…”
mentioning
confidence: 99%